2022
DOI: 10.1021/acs.analchem.1c04541
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Enzyme-Coronated Gold Nanoparticles with an Erythrocyte Membrane for Highly Selective Glucose Assays

Abstract: Colorimetric glucose sensors using enzyme-coronated gold nanoparticles have been developed for high-throughput assays to monitor the blood glucose levels of diabetic patients. Although those sensors have shown sensitivity and wide linear detection ranges, they suffer from poor selectivity and stability in detecting blood glucose, which has limited their practical use. To address this limitation, herein, we functionalized glucose-oxidase-coronated gold nanoparticles with an erythrocyte membrane (EM-GOx-GNPs). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous studies have reported various biosensors for detecting Glu using redox reactions with GOx. , However, in contrast, measuring GOx using Glu and other sugars has been rarely reported. , Herein, we tested which saccharides could efficiently recognize GOx. First, Glu@CPS, Fru@CPS, Mal@CPS, Lac@CPS, and Suc@CPS were prepared by coating the CPS with various saccharides, such as Glu, Fru, Mal, Lac, and Suc (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported various biosensors for detecting Glu using redox reactions with GOx. , However, in contrast, measuring GOx using Glu and other sugars has been rarely reported. , Herein, we tested which saccharides could efficiently recognize GOx. First, Glu@CPS, Fru@CPS, Mal@CPS, Lac@CPS, and Suc@CPS were prepared by coating the CPS with various saccharides, such as Glu, Fru, Mal, Lac, and Suc (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose (Glu) is a vital component of human physiological fluids, with elevated concentrations posing a significant threat to health through the potential onset of diabetes . Consequently, a variety of biosensors for glucose measurement have been developed. Among these, glucose oxidase (GOx), produced by fungi such as Aspergillus niger, has emerged as a primary enzyme in biosensors for glucose detection. GOx not only catalyzes the oxidation of glucose into hydrogen peroxide and d-glucono-δ-lactone but also possesses unique characteristics such as specific activity, thermal stability, pH tolerance, and substrate specificity. These attributes have led to widespread utilization and growing interest in GOx across various industrial sectors, including food, clinical diagnostics, and biotechnology. Concurrently, research utilizing GOx is actively progressing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2e, f and S 7 ). Via KPFM, we measured the physicochemical characterizations of the BEETLES 2 membrane, which was negatively charged due to the negatively charged phospholipids in RBCM 29 , 30 . In contrast, the BEETLES 2 membrane with 4% RBCM showed a relatively positively charged surface compared to that with 2% RBCM.…”
Section: Resultsmentioning
confidence: 99%
“…To break the hurdles of the aforementioned techniques, nanomaterial-based colorimetric assays have recently attracted academic and industrial attention due to the merits of their simple operation, low cost, easy visualization, and availability for onsite detection. Recently, a 3,3′,5,5′-tetramethylbenzidine (TMB)–H 2 O 2 colorimetric system has been widely used in bioanalysis and clinical application. , To further strengthen the applicability of detection, the gold nanoparticles (AuNPs) have become an ideal candidate as an enzyme-mimicking nano-catalyst because of their high stability, easy use, and wider working temperature and pH values than most natural enzymes (e.g., horseradish peroxidase, superoxide dismutase, esterase, etc. ), which are more conducive to onsite determination. For example, Tang et al developed a self-powered temperature sensor based on Seebeck effect transduction induced by the one-electron oxidation product (ox-TMB) of TMB, which could be applied to α-fetoprotein photothermal-thermoelectric analysis .…”
Section: Introductionmentioning
confidence: 99%